2007
DOI: 10.1088/1126-6708/2007/04/065
|View full text |Cite
|
Sign up to set email alerts
|

Classical open string integrability

Abstract: We present a simple procedure to construct non-local conserved charges for classical open strings on coset spaces. This is done by including suitable reflection matrices on the classical transfer matrix. The reflection matrices must obey certain conditions for the charges to be conserved and in involution. We then study bosonic open strings on AdS 5 ×S 5 . We consider boundary conditions corresponding to Giant Gravitons on S 5 , AdS 4 × S 2 D5-branes and AdS 5 × S 3 D7-branes. We find that we can construct the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(104 citation statements)
references
References 60 publications
3
99
0
Order By: Relevance
“…For the four dimensional case considered in [7], as far as we know, there are no higher loop computations in the gauge theory side to obtain the higher order Hamiltonian and check the integrability at higher loop order. In the dual open string theory side, strong evidence for the integrability of the classical worldsheet theory was obtained in [33] by constructing non-local conserved charges in the full bosonic sector. This suggested that the field theory in the planar limit is integrable in the strong coupling regime.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For the four dimensional case considered in [7], as far as we know, there are no higher loop computations in the gauge theory side to obtain the higher order Hamiltonian and check the integrability at higher loop order. In the dual open string theory side, strong evidence for the integrability of the classical worldsheet theory was obtained in [33] by constructing non-local conserved charges in the full bosonic sector. This suggested that the field theory in the planar limit is integrable in the strong coupling regime.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…and which is solved only by using the mass-shell condition (29) and in addition imposing the equation…”
Section: Reflection Matricesmentioning
confidence: 99%
“…Evidence for classical open string integrability in the giant graviton background, from the world-sheet point of view has also recently been presented in [28]. For a detailed analysis of various other recently discovered aspects of open string dynamics and their gauge theory duals we shall refer to [27].…”
Section: Open Spin Chains and Branes In Symmentioning
confidence: 97%